The 5 K run in popular fiction: Reading about parkrun and couch to 5 K - Turner, Ellen (Frontiers in Sports and Active Living, 2023)
Recent years have witnessed great interest in mass-participation running events (1), and organisations such as parkrun and fitness programmes like Couch to 5 K, have been instrumental in enabling participation for inexperienced runners. Concomitant with this has been a number of fictional works which centre on the 5 K run. I contend that exploring fictional texts can offer a fresh take on how movements such as parkrun and Couch to 5 K have entered the popular imagination. The four texts explored are Wake's Saturday Morning Park Run (2020), Park's A Run in the Park (2019), Boleyn's Coming Home to Cariad Cove (2022), and James's I Follow You (2020). The analysis is arranged thematically around the categories of health promotion, individual transformation, and community building. I argue that these texts frequently operate as health promotion tools and can help familiarise would-be runners with how parkrun and Couch to 5 K work.